Patos de Minas na rota do Tecnicismo: Escola Polivalente como construtora de mentes para o progresso (1970 – 1985) - Chaves, Cléberton Luiz (2020)
The present study is intended to address the professional education even if, in a brief way, trying to understand the implementation of polyvalent schools in Brazil, in the 1970s, as well in the state of Minas Gerais, focusing mainly on the city of Patos de Minas. Polyvalent schools (Multipurpose Gymnasiums) are an American educational model of high schools. In Brazil, issues involving labor were always discussed by political and economic authorities. The military took those issues to the educational environment also. The project on polyvalent schools, in conjunction with law 5.692/1971, aimed to implant the professional education at Brazilian schools. Resolution number 925/1970 from the government of the state Minas Gerais, moreover, provided for the polyvalent school model for all education network. During the military regime, Brazil’s economic vision has changed. The new economic policy adopted a strategy of international capital appreciation. The consequence was an industrial boom where man powered labor was highly valued. Through trade agreements with foreign capital, like USAID (United States Agency for International Development) and BIRD (Inter-American Development Bank), MEC (Ministry of Education and Culture) and PREMEM (High School Expansion and Improvement Program), Brazil implements the polyvalent schools model. In the city of Patos de Minas, the polyvalent school was set up in 1971 - first phase of implementation. The school was known as “Escola Estadual Professora Elza Carneiro Franco”, known as “O Polivalente”. In a short period of time, the school tried to evoke vocational aspects which are necessary to the world of employment and to serve the Patos de Minas community, in terms of education and culture. Public authorities and their political handling in relation to the proper functioning of the school were evoked issues in this study too. Lots of questionings are made in this study. In a methodological and scientific way, answers were investigated from traces found in bibliographic and documental sources, mainly newspapers and iconography. In the city of Patos de Minas, the polyvalent school managed to combine practical subjects with theoretical knowledge. The school tried to highlight the purpose of education in relation to vocational survey. School subjects as Agricultural Techniques, Industrial Techniques, Commercial Techniques and Housekeeping Education had been added to the academic curriculum. The polyvalent school in Patos de Minas was a differentiated educational institution during the time it had been under the supervision of PREMEM. In 1976, the polyvalent school projects were extinguished, only the school in Patos de Minas still tried to survive, maintaining the standards and objectives for which it was designed. But it didn’t last long as the government of the state of Minas Gerais decided to fully absorb all polyvalent schools into the state public-school educational system network.